LETTING OFF STEAM: TRADE UNIONS AND RAILWAY WORKERS' DISCONTENT WITH THE KHRUSHCHEVIAN SOCIAL CONTRACT - Cooper, Magnus Bowman (Nazarbayev University School of Sciences and Humanities, 2025)
Following the death of Stalin on March 5 1953, railway workers in Soviet Kazakhstan were presented with a new model for Soviet society, the productivist social contract: an implicit agreement that in return for increased productivity the state would provide workers with an increased standard of living through the provision of welfare. The purpose of this paper is to examine how railway workers on Turksib, a group shaped by the experiences of Stalinist industrialisation, reacted to this social contract, and how trade unions acted as a venue where the social contract could be negotiated. Drawing on documents from the Turksib trade union from 1953 to 1963, this thesis reveals that workers’ complaints seem to show that the productivist social contract created a catch 22, as on the one hand increased standards of living were dependent on productivity, and on the other workers' complaints about the shortcomings of the productivist social contract argued that they relied on these welfare provisions in order to work well and improve productivity. Workers blamed the shortcomings of the social contract on local management, as they were the most immediate representatives of the state on the ground and criticism of the central state was impossible. Management in turn was largely hamstrung in their ability to address these shortcomings by material limitations created by the central state and the command economy. The central state in turn encouraged this scapegoating as a method of redirecting workers’ discontent, and trying to convince workers that it was “for them”. Management were also frustrated in their attempts at combating the poor labour discipline that contributed to low productivity, a continued manifestation of workers’ tactics of individualised control developed during Stalinist industrialisation. Reforms during the Khrushchev period left management bereft of their traditional tools for disciplining the workforce, and they themselves would again be scapegoated for their own workers' poor discipline, as problems of discipline were portrayed as a failure of local officials to properly educate workers. The Khrushchev regime ultimately failed to persuade workers to acquiesce to the productivist social contract, creating a situation where workers were able to have their, albeit meager, cake and eat it too, continuing to use their tactics of individual control scot free and passing the blame for low productivity on to local management.
Keywords: USSR; Soviet Union; Railways; Turksib; Trade Unions; Khrushchev; The Thaw; Kazakhstan; Workers; Railway Workers; Type of access: Embargo